CHANGES IN "CROWNS" IN TOPOLOGICAL ALGEBRAS OF FUNCTIONS - Khudoyan, Tigran M.; Karakhanyan, Martin I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2025)
In this work, for topological algebras of continuous complex-valued functions defined on a locally compact, the change in the topological "crown" of such algebra is studied depending on the topology introduced in it. Note that the concept of the "crown" was previously studied in works [1-3]. However, the concept of the topological "crown" for topological algebras of functions is introduced for the first time in work [3]. In fact, the topological "crown" is the set of all those linear multiplicative functionals that are not continuous on the given topological algebra.
Keywords: topological "crown"; algebra; space of maximal ideals; continuous functions; linear multiplicative functionals